Towards More Sustainable Hazelnut Supply Chains in Azerbaijan: Competitiveness through Post-Harvest Management and Quality Control - Jafarli, Dinara (My University, 2026)
The Azerbaijani hazelnut sector has grown significantly in recent years, supported by rising export demand and the national priority of developing non-oil agricultural products. Despite this progress, post-harvest management and quality control continue to create important challenges for product quality, food safety, and export competitiveness. This study focuses on the role of harvesting, drying, storage, sorting, and quality control in the performance of Azerbaijan’s hazelnut supply chain. A qualitative case study approach was used, combining secondary sources with primary data collected through a semi-structured interview and follow-up clarifications with a representative of Agrarco, one of the major hazelnut producers and exporters in Azerbaijan. The findings suggest that the main bottlenecks are related to moisture management, drying practices, storage conditions, aflatoxin risk, limited early detection, and coordination with external suppliers. These issues can contribute to quality deterioration, shipment rejection, financial losses, and weaker export reliability. Comparative insights from Türkiye also show that competitiveness depends not only on production volume, but also on stronger post-harvest infrastructure, closer producer-exporter coordination, and more consistent quality assurance systems. The study’s findings also contribute to the discussion on the sustainability of agricultural supply chains by showing the environmental, economic, and social implications of post-harvest inefficiencies, quality losses, and food safety risks in the Azerbaijani hazelnut sector. The study concludes that Azerbaijan can strengthen the long-term competitiveness and sustainability of its hazelnut sector by improving drying and storage systems, strengthening supplier coordination, enhancing early quality detection, and treating quality control as an integrated supply chain process rather than only a final export checkpoint.
Keywords: hazelnut supply chain; post-harvest management; quality control; aflatoxin; export competitiveness; Azerbaijan